Determinantes de intención de adopción del e-commerce por parte de las PYMES agroexportadoras de España y Perú - Perez Sava, Gianinna Ely (2023)
The objective of this study is to analyze the influence of the determinants of e-commerce adoption intention by agro-exporting SMEs in Spain and Peru. The following determinants were analyzed: attitude, subjective norms, perceived behavioral control (PBC), facilitators and barriers. These influence the adoption of e-commerce and facilitate its implementation. The background used to estimate respondents' favorable reception of e-commerce is a model based on the Theory of Planned Behavior, which has been extended to include perceived facilitators and barriers as antecedents of attitude towards e-commerce adoption. Agro-exporting SMEs from Spain and Peru participated. The data analysis technique used was Structural Equation Modeling through Partial Least Squares, for which SmartPLS software was used. This software shows the differences between the groups and will allow more significant estimates to be made using the bootstrapping method. The main conclusions of the study are: (1) There is a positive influence between attitude, subjective norm, perceived behavioral control and intention to use e-commerce. In particular, attitude turned out to be the strongest predictor of the intention to adopt e-commerce in Peru. In Spain it is perceived behavioral control; (2) the Theory of Planned Behavior has been successfully used to explain the e-commerce adoption process among managers or bosses in Spain and Peru; (3) there are significant relationships between facilitating factors and barriers and attitude towards e-commerce use; (4) there is a strong and significant relationship between attitude and intention to use e-commerce. Small and medium-sized enterprises in developing countries can use the results to boost e-commerce adoption.